Systemic administration of orexin A ameliorates established experimental autoimmune encephalomyelitis by diminishing neuroinflammation - Laurine Becquet; Catalina Abad; Mathilde Leclercq; Camille Miel; Laetitia Jean; Gaëtan Riou; Alain Couvineau; Olivier Boyer; Yossan‐Var Tan (2019)
Orexins (hypocretins, Hcrt) A and B are GPCR-binding hypothalamic neuropeptides known to regulate sleep/wake states and feeding behavior. A few studies have shown that orexin A exhibits anti-inflammatory and neuroprotective properties, suggesting that it might provide therapeutic effects in inflammatory and neurodegenerative diseases like multiple sclerosis (MS). In MS, encephalitogenic Th1 and Th17 cells trigger an inflammatory response in the CNS destroying the myelin sheath. Here, we investigated the effects of peripheral orexin A administration to mice undergoing experimental autoimmune encephalomyelitis (EAE), a widely used model of MS.Mice were subcutaneously immunized with myelin oligodendrocyte glycoprotein peptide (MOG)35-55 in CFA. Mice were treated intraperitoneally for five consecutive days with either PBS or 300 μg of orexin A starting at a moderate EAE score. Molecular, cellular, and histological analysis were performed by real-time PCR, ELISA, flow cytometry, and immunofluorescence.Orexin A strongly ameliorated ongoing EAE, limiting the infiltration of pathogenic CD4+ T lymphocytes, and diminishing chemokine (MCP-1/CCL2 and IP-10/CXCL10) and cytokine (IFN-γ (Th1), IL-17 (Th17), TNF-α, IL-10, and TGF-β) expressions in the CNS. Moreover, orexin A treatment was neuroprotective, decreasing demyelination, astrogliosis, and microglial activation. Despite its strong local therapeutic effects, orexin A did not impair peripheral draining lymph node cell proliferation and Th1/Th17 cytokine production in response to MOG35-55 in vitro.Peripherally-administered orexin A ameliorated EAE by reducing CNS neuroinflammation. These results suggest that orexins may represent new therapeutic candidates that should be further investigated for MS treatment.